Dinosaurs and other reptiles from the Mesozoic of Mexico - Rivera-Sylva, Héctor E., 1978-; Carpenter, Kenneth, 1949-; Frey, Eberhard, 1953- (Life of the past., 2014)
This overview of dinosaur discoveries in Mexico synthesizes current information about the geography and environment of the region during the Mesozoic when it was the western margin of the ancient continent of Pangea. The book summarizes research on various groups, including turtles, lepidosauromorphs, plesiosaurs, crocodyliforms, pterosaurs, and last but not least, dinosaurs. In addition, chapters focus on trackways and other trace fossils and on K/P boundary (the Chicxulub crater, beneath the Gulf of Mexico, has been hypothesized as the site of the boloid impact that killed off the dinosaurs).